The Importance of Cooperative Culture and Communication as Success Factors for Savings and Credit Cooperatives in Neiva (Huila) - Huergo Tobar, Pedro Luis; Artunduaga Calderón, Diva María (Cooperativismo & Desarrollo, 2014)
This research examines the importance and management of cooperative culture and the communication between its leaders and coworkers in the savings and credit cooperatives (cac) in Neiva. It also seeks to determine whether identifying elements that apply in communication, and also identifying problems or negative situations that occur in the internal communication process, are success factors. A wide knowledge and understanding of cooperative culture was found among leaders and coworkers. Additio- nally, the communication channels are flexible, fluid and generate a good organizational environment, bringing about better service provision for associates, and driving an increase in their social base.